2018
DOI: 10.3847/2041-8213/aaeb2c
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Environmental Dependence of Molecular Gas Content in a Distant X-Ray Cluster at z = 2.51

Abstract: We present a census of the molecular gas properties of galaxies in the most distant known X-ray cluster, CLJ1001, at z=2.51, using deep observations of CO(1-0) with JVLA. In total 14 cluster members with M * > 10 10.5 M are detected, including all the massive star-forming members within the virial radius, providing the largest galaxy sample in a single cluster at z > 2 with CO(1-0) measurements. We find a large variety in the gas content of these cluster galaxies, which is correlated with their relative positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 50 publications
4
118
0
Order By: Relevance
“…In contrast, it has been shown that at high-redshift massive galaxies (often residing in the proto-clusters, i.e., the progenitors of the clusters at redshift zero) can have efficient star formation (e.g. Miller et al 2018;Wang et al 2018). Because the lognormal parametrisation leaves a tail on the high mass end, it might mimic this effect, and the choice of the this shape is therefore justified.…”
Section: From Accretion Onto the Dark Matter Haloes To Sfrmentioning
confidence: 99%
“…In contrast, it has been shown that at high-redshift massive galaxies (often residing in the proto-clusters, i.e., the progenitors of the clusters at redshift zero) can have efficient star formation (e.g. Miller et al 2018;Wang et al 2018). Because the lognormal parametrisation leaves a tail on the high mass end, it might mimic this effect, and the choice of the this shape is therefore justified.…”
Section: From Accretion Onto the Dark Matter Haloes To Sfrmentioning
confidence: 99%
“…In addition, a comparison with galaxies in the field, in clusters, and in other proto-clusters can provide insights into the role played by the environment. To this end, we collected CO data from the literature for galaxies in clusters (62 galaxies in 11 clusters, Wang et al 2018;Rudnick et al 2017;Stach et al 2017;Aravena et al 2012;Casasola et al 2013;Castignani et al 2018;Coogan et al 2018;Hayashi et al 2017;Webb et al 2017) and in proto-clusters (16 galaxies in four proto-clusters, Dannerbauer et al 2017;Ivison et al 2013;Tadaki et al 2014;Lee et al 2017), and of SMGs and AGN in the z = 1-3 redshift range (31 SMGs, 15 AGN, and 38 obscured AGN, Perna et al 2018). In order to represent normal star-forming galaxies and SB galaxies, we used the SFR-M rela-tion 5 from Speagle et al (2014), and the L CO − L IR relation from MS and SB galaxies as derived by Sargent et al (2014) 6 For estimating molecular gas masses, we converted all high transition CO luminosities to L CO(1−0) , when not available, using the median brightness temperature ratios derived by Bothwell et al (2013).…”
Section: Co Line Propertiesmentioning
confidence: 99%
“…Gas masses are derived using M gas = α CO L CO(1−0) . The adopted α CO value for each galaxy is that reported in earlier studies (Tadaki et al 2014;Dannerbauer et al 2017;Wang et al 2018;Lee et al 2017;Ivison et al 2013), and had been fixed to either α CO = 0.8, typical of SB galaxies, or α CO = 4.0-4.36, typical of normal SFGs. We remind that we consider as an SB any source with SFR > 3 × SFR MS , but this definition might not match what was found in other published samples.…”
Section: Co Line Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for direct, resolved stripping of CO has also been observed in a handful of galaxies (Lee & Chung 2018;Moretti et al 2018;Cramer et al 2020;Jáchym et al 2019), while additional cases of molecular disturbances have been found in Virgo (Lee et al 2017a). Broadly speaking, at intermediate and higher redshifts, reports are even more varied, with some suggestions that (proto)clusters favour H2-poor galaxies (Jablonka et al 2013;Castignani et al 2018;Coogan et al 2018), others that they favour H2-rich galaxies (Noble et al 2017;Hayashi et al 2018), others that they favour H2normal galaxies (Dannerbauer et al 2017;Lee et al 2017b;Rudnick et al 2017;Darvish et al 2018;Wu et al 2018), or a mass-dependent/phase-space-dependent combination thereof (Hayashi et al 2017;Wang et al 2018;Tadaki et al 2019).…”
mentioning
confidence: 99%